Production performance of four lines of Japanese quail reared under tropical climatic conditions of Tamil Nadu, India - Arunrao, Keche Vishal; Kannan, Duraisamy; Amutha, Ramasamy; Thiruvenkadan, Aranganoor Kannan; Yakubu, Abdulmojeed (Frontiers in Genetics, 2023)
This study was conducted on the growth and other production performance of four different lines (L1, L2, L3 and L4) of Japanese quail (Cortunix japanoica) maintained under tropical climatic conditions of Tamil Nadu, India. The data on various production and reproduction parameters were collected and analysed. The results revealed a highly significant difference (P<0.01) in body weight from hatch to 5th week of age, where the highest value was recorded in L3 (235.31 g) and the lowest in L4 (203.62 g). The cumulative 5th week feed conversion ratio showed non-significant difference (P>0.05) at first and second week, and highly significant difference (P<0.01) from third to fifth week of age. The age (P<0.05) at 50 per cent egg production was 60.2 (L4), 61.4 (L2), 65.1 (L3) and 66.0 (L1) days. The highest bodyweight (g) (P<0.01) during the laying period (at 15 weeks of age) was observed in L2 (327.08) followed by L3 (326.54), L1 (309.24) and L4 (288.69) lines, respectively. The mean egg weight (g) of different lines showed non-significant difference (P>0.05) at all weeks, except at 11th week of age (P<0.01). The mean feed consumption (g)/bird/day differed significantly (P<0.01) from 6th to 16th week of age, except at 6th and 8th week of age, where it was non-significant (P>0.05). The overall feed efficiency/dozen of eggs (from 6th to 16th weeks) (P>0.05) ranged from 1.33 (L1) to 1.98 (L3). The livability from 6 to 16 week of age was 100 per cent in all the lines. In order to boost Japanese quail production in the tropics, L3 and L4 may be selected for body weight and egg production, respectively.